2008
DOI: 10.1021/jp7119334
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of Atmospheric Aerosol Constituents and Precursors in the 7−15 eV Energy Region: Experimental and Theoretical Study

Abstract: Photoionization mass spectrometry (PIMS) has been used to study the dissociative ionization of three anthropogenic atmospheric aerosol precursors (o-xylene, 2-methylstyrene, indene) and five of their main atmospheric degradation products (o-tolualdehyde, 2-methylphenol, o-toluic acid, phthalic acid, and phthaldialdehyde). Ionization and fragment appearance energies have been experimentally determined in the 7-15 eV photon energy regime. Moreover, intensive ab inito quantum chemical calculations have been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Note that the obtained fragment ion appearance energies (AEs) correspond to effective thermochemical energy values. As has been discussed in more detail earlier by Gaie-Levrel et al 59 there are three main factors for the possible difference between the effectively measured AE and the 0 K value: (i) the limited detection sensitivity, (ii) the thermal energy stored in the parent neutral, (iii) fragmentation dynamics (possible activation barriers, formation of vibrationally excited fragments) also influence the effective AE and might lead to a substantial energy shift, E, yielding a too-high AE value. The magnitude of E is difficult to determine with the current experimental setup, or estimate with statistical models based on the existence of a transition state, and therefore is beyond the scope of this work.…”
mentioning
confidence: 73%
“…Note that the obtained fragment ion appearance energies (AEs) correspond to effective thermochemical energy values. As has been discussed in more detail earlier by Gaie-Levrel et al 59 there are three main factors for the possible difference between the effectively measured AE and the 0 K value: (i) the limited detection sensitivity, (ii) the thermal energy stored in the parent neutral, (iii) fragmentation dynamics (possible activation barriers, formation of vibrationally excited fragments) also influence the effective AE and might lead to a substantial energy shift, E, yielding a too-high AE value. The magnitude of E is difficult to determine with the current experimental setup, or estimate with statistical models based on the existence of a transition state, and therefore is beyond the scope of this work.…”
mentioning
confidence: 73%
“…In addition, a fragment AE can be subject to a substantial kinetic shift, ΔE kin since at threshold, the reaction might be too slow to be observed. These effects were discussed in more detail by Schwell and co-workers in [49,50]. Such kinetic shifts can be estimated by statistical models based on the possible existence of a transition state along the reactive pathways (see for example [51]).…”
Section: Photoionization Mass Spectrometry (Pims)mentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) have been of great interest in many research areas, due to their importance in the interstellar medium, 44,45 environment, 46 combustion, 47 and semiconductors 48,49 . Compared with the extensive studies on simple aliphatic hydrocarbons, 25–31,50,51 reliable measurements of PICSs for aromatic hydrocarbons are still limited 52–57 . DeWitt et al 53 determined the relative PICSs of some monocyclic aromatics using femtosecond laser ionization and time‐of‐flight mass spectrometry (TOF‐MS).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the PICSs of benzene and a series of other aromatic hydrocarbons were measured exclusively at 10.5 eV 55,56 . Another study reported the relative photoionization curves of o ‐xylene, 2‐methylstyrene, indene and five atmospheric degradation products in the photon energy range of 7–15 eV 57 . However, PICSs of only a few aromatic compounds were obtained at 10.5 eV 57 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation